23-year-old female with dyspnea, hematuria, and seizure progressing to respiratory failure - Yaqoob, M.; EI-Sameed, Y.A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Takayasu arteritis is a rare chronic inflammatory disease on unknown etiology.We report a 23-year old female who presented with fever, shortness of breath and abdominal pain. Shortly thereafter the patient developed hematuria, hemoptysis and seizure progressing to respiratory failure. She was found to have aortitis and alveolar hemorrhage. We discuss the clinical manifestations and the diagnostic work up of Takayasu arteritis. The patient’s response to therapy and a discussion on treatment modalities of the disease are also included in the report